Towards a Sustainable and Healthy Work Environment –Lessons Learned from the Unprevented Exposure of Miners to Coal Dust. (2015) - Tello, Linda M.; Grau, David
Abstract: Particularly challenging for the development of meaningful performance baselines associated with health hazards in construction is the lack of statistics on the number and on the understanding of chronic occupational illnesses within the sector. That health issues from the continued exposure to hazards does not commonly result in an immediate but in a long-term condition likely evident once workers are not active in the industry explains such lack of and understanding. By exploring the origins and consequences of the prevalent attitudes within the coal industry that facilitated the excessive exposure of miners to coal dust, prospects for mitigating potential negative outcomes of present and future interactions between worker and work environment can be assessed. Thus, lessons learned from the unprevented exposure of coal miners are analyzed and discussed in this article with the expectation that they can be used to mitigate the unprevented exposure of construction workers to health hazards.